'All in One Stroke': Grimms' Fairy Tales and the TV-Production of a New Germany. (September 2015) - Wölfel, Ute
<x content-type="archive" xml:space="preserve">Abstract</x> The article looks at the most recent TV adaptations of the Grimms' fairy tales by public broadcasting. Realized and marketed as a season which started in 2008, the thirty-four currently existing individual films constitute a significant national project that presents highly appealing notions of the German past to an audience divided over national conflict and demands of globalization. With children and adolescents at the centre, the films offer the young as a generation of moral superiority that facilitates social harmony and moral consensus. This post-unification utopia is beautifully realized on screen but rests on very conservative assumptions about gender, social driving forces, and political order.